The stability of immiscible viscous fingering in Hele-Shaw cells with spatially varying permeability - Jackson, S.J.; Power, H.; Giddings, Donald; Stevens, D. (Elsevier, 2017)
In this paper, we investigate the stability of immiscible viscous fingering in Hele-Shaw cells with spatially varying permeability, across a range of capillary numbers. We utilise a coupled boundary element - radial basis function (BE –RBF) numerical method that adapts and moves with the growing interface, providing an efficient, high accuracy scheme to track the interfacial displacement of immiscible fluids. By comparing the interfacial evolution and growth rate in varying permeability cells to that in uniform cells, we can assess the relative stability of the perturbations as a consequence of the variable permeability.